Vejen fra tvang til frihed i Grundtvigs liv og forfatterskab - Michelsen, William (Grundtvig-studier, 1991)
The Way from Force to Freedom in Grundtvig’s Life and Writings By William Michelsen. As it was shown by Kaj Thaning in Grundtvig Studies, 1981, Grundtvig, in 1825, made the discovery, new at the time, that the Christian church is older than The New Testament. He utilized the discovery to claim that the Apostolic Confession is the criterion of genuine Christianity, and the same year, in .The Rejoinder of the Church., he used it against H.N. Clausen, Professor of Theology, in an attempt to force him to lay down his office if he did not admit and apologize for his ‘scandalous teaching’. However, Grundtvig was charged instead, and, in 1826, received a sentence for libel of Clausen, and therefore resigned his office as a clergyman himself. Nonetheless, from 1832 to his death in 1872, Grundtvig became the most unswerving supporter of freedom in Danish spiritual life. The standpoint is clearly expressed in .Norse Mythology., 1832, and the same year Grundtvig was permitted to preach in the state church, from 1839 until his death as a vicar of Vartov Church. How can this change of attitude on Grundtvig’s part be explained?The assertion of the present article is that the apparently dramatic changes in Grundtvig’s attitude to freedom are consistent on a more fundamental level, partly depending on his religious development, partly on his concept of freedom which differed from the usual philosophical thinking of his time.Already before his birth, his parents had decided that Grundtvig was to become a clergyman, and in 1810, when his father demanded that he should make a personal application to the King for permission to be his father’s personal curate, he consequently felt force to submit, though it had always been his own wish to be a historian. So he saw himself as obliged through his ordination to defend genuine Christianity against any kind of Rationalist falsification - first on the basis of Luther scripturalism, and from 1825 on the basis of the Apostolic Confession. When H.N. Clausen did not lay down his office, Grundtvig had to lay down his.How then can it be explained that already in 1831 Grundtvig admitted that one must allow one’s opponent the same freedom to speak as one demands for oneself - the following year, even within the same state church. The explanation is to be found in Grundtvig’s experiences from his journeys to England, perhaps in particular from a conversation with Clara Bolton in 1830. More particularly the present article claims that his attitude rests on the assessment of John Wesley’s withdrawal from the state church, proposed by Grundtvig in his ‘ Prospect of the World Chronicle’, 1817: it was not necessary because Wesley was not - like Luther – ‘excommunicated’ from the church, but only ‘excluded from the office of teaching’ - the same situation as Grundtvig felt he was in from 1826 to 1832.Grundtvig’s characteristic concept of freedom can be traced as far back as to 1814 (cf. Grundtvig Studies, 1986, pp. 8-9): Man is created with a will of his own, which may be either obedient or disobedient to the will of the Creator, and which is therefore free. Man, however, is not an independent being in the universe. Grundtvig was an opponent of the usual notion that the human personality is free by virtue of his reason.